OC-16 - Neutrophil extracellular traps and tissue factor-bearing microvesicles: a liaison dangereuse causing overt DIC in cancer patients?. Issue 140 (April 2016) - Hell, L.; Thaler, J.; Martinod, K.; Ay, C.; Posch, F.; Wagner, D.D.; Pabinger, I.
Abstract : Introduction: Overt disseminated intravascular coagulation (DIC) is a systemic process characterized by excessive coagulation activation and fibrinolysis that may occur in cancer patients. The underlying pathomechanisms are still poorly understood. Recent experimental studies found an important role for the interaction between procoagulant neutrophil extracellular traps (NETs) and tissue factor (TF) in the pathogenesis of thrombosis. Aim: To investigate whether NETs and TF-bearing microvesicles (MVs) play a central role in cancer-related overt DIC. Materials and Methods: Twenty-eight cancer patients with overt DIC (ISTH score ≥ 5, 14 females, median age: 62 years [range: 21-80], 13 with solid tumors, 15 with acute leukemia) and 28 matched healthy controls were included. NET formation parameters (plasma DNA and nucleosomes), MVassociated TF activity, and routine coagulation parameters were determined at study inclusion. In 11 patients with acute myeloid leukemia (AML), follow-up measurements were also performed. Results: Plasma DNA, nucleosomes, and MV-TF activity were highly elevated in patients with cancer-related DIC compared to healthy individuals (all p-values < 0.001). Strong correlations were found between plasma DNA and nucleosomes (Spearman correlation-coefficient: r = 0.68), nucleosomes and MV-TF activity (r = 0.62), and DNA and MV-TF activity (r = 0.57). In multivariate regression, altered routine coagulation parameters were highly associated with NET parameters and MV-TF activity. In detail, a doubling in plasma DNA was associated with a 7.6% decrease in fibrinogen (p = 0.012), a 15.3% decrease in platelet count (p = 0.002), a 3.9% decrease in prothrombin time (p = 0.014), and a 41.0% increase in D-dimer (p < 0.001). A 10% increase in nucleosomes was associated with a 3.1% decrease in fibrinogen (p < 0.001), a 5.0% decrease in platelet count (p < 0.001), a 1.0% decrease in prothrombin time (p < 0.009), and a 112.7% increase in D-dimer (p < 0.001). A 10% increase in MV-TF activity was associated with a 4.9% decrease in fibrinogen (p < 0.001), a 7.1% decrease in platelet count (p < 0.001), a 1.3% decrease in prothrombin time (p < 0.001), and a 15.5% increase in D-dimer (p < 0.001). After initiation of chemotherapy in AML patients, NET parameters and MV-TF activity decreased significantly (nucleosomes: 3.3-fold decrease and normalization after 1 week; DNA: 1.2-fold decrease after 1 week and 1.5-fold decrease after 1 month; MV-TF activity: 10-fold decease after 1 week and normalization after 1 month) (Figure 1), and routine coagulation parameters improved. Fig. 1 (Abstract OC-16) Plasma nucleosomes (A), DNA (B), and MV-TF activity (C) in AML patients with overt DIC, 1 week, and 1 month after initiation of chemotherapy, and in healthy controls. Conclusions: Our results add to experimental studies that have investigated the interaction between NETs and TF. Taken together, evidence indicates the presence of a liaison dangereuse between NETs and TF-bearing MVs, which could be the underlying cause of cancer-related overt DIC.